KEMAJUAN HAK ASASI MANUSIA ATAS PELARANGAN ANALOGI DALAM PENETAPAN TINDAK PIDANA BERDASARKAN PASAL 1 AYAT 2 KUHP NASIONAL - S, Laurensius Arliman; Hutajulu, Andreas Fransiskus (Ensiklopedia of Journal, 2025)
Abstract: This study aims to analyze the progress of human rights (HR) in national criminal law through the prohibition of using analogy in determining an act as a criminal offense, as reflected in Article 1 Paragraph 2 of the new Indonesian Criminal Code (KUHP Nasional). The research uses a normative legal method with statutory and conceptual approaches. In the context of modern criminal law, the prohibition of analogy is considered a manifestation of the principle of legality (nullum crimen sine lege), ensuring legal certainty and protecting the fundamental rights of individuals from arbitrary state actions. By disallowing analogy, no individual can be punished unless based on a previously established law. This represents significant progress in the protection of human rights, especially in ensuring that criminal law is not used as a tool of repressive power. The findings indicate that Article 1 Paragraph 2 of the KUHP affirms human rights principles aligned with international instruments such as the ICCPR. Therefore, the prohibition of analogy in national criminal law is not merely a formal legal step, but an ethical milestone in the enforcement of criminal justice.Keywords: Human Rights, Analogy, National Criminal Code, Principle of Legality.